KETERKAITAN ANTARA IJTIHAD DAN ETIKA DALAM USHUL FIQH - Mareta Asprianti Safitri; Muhammad Nasirudin; Hafidz Taqiyuddin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
This research is to explain the relationship between the ijtihad process and the ethical values ​​that a mujtahid must have, including aspects of the discussion of ijtihad in ushul fiqh, and outlining the ethical principles that a mujtahid must have. The method in this study uses a qualitative approach that is library-based, data sources are collected from journals, books and other supporting materials that discuss ijtihad in ushul fiqh. Ijtihad plays an important role in the development of Islamic law, especially in facing the transformations that occur in technology, social, and culture as well as globalization. By using ijtihad, Islamic teachings remain relevant throughout time and can answer various questions that arise in the current era. However, ijtihad also has limitations; it must be carried out by people who qualify as mujtahid and must not conflict with the basic principles of Islamic teachings. To achieve broader results and in accordance with the needs of the community, ijtihad is currently carried out not only individually but also collectively through fatwa institutions. In conclusion, ijtihad functions as an important link between classical Islamic literature and contemporary conditions. Ethics are also an important foundation in ijtihad, because a mujtahid must be ethical for the sake of welfare, justice, and honesty for the benefit of all.